Biochemistry, proteomics, and phosphoproteomics of plant mitochondria from non-photosynthetic cells - Havelund, Jesper F.; Thelen, Jay; Møller, Ian M. (Frontiers in Plant Science, 2013)
Mitochondria fulfill some basic roles in all plant cells. They supply the cell with energy in the form of ATP and reducing equivalents (NAD(P)H) and they provide the cell with intermediates for a range of biosynthetic pathways. In addition to this, mitochondria contribute to a number of specialized functions depending on the tissue and cell type, as well as environmental conditions. We will here review the biochemistry and proteomics of mitochondria from non-green cells and organs, which differ from those of photosynthetic organs in a number of respects. We will briefly cover purification of mitochondria and general biochemical properties such as oxidative phosphorylation. We will then mention a few adaptive properties in response to water stress, seed maturation and germination and the ability to function under hypoxic conditions. The discussion will mainly focus on Arabidopsis cell cultures, etiolated germinating rice seedlings and potato tubers as model plants. It will cover the general proteome as well as the posttranslational modification protein phosphorylation. To date 64 phosphorylated mitochondrial proteins with a total of 103 phosphorylation sites have been identified.